Position paper: leveraging non-human primate (NHP) specificities to accelerate Parkinson’s disease and ageing research - Erwan Bezard; Rozalyn M. Anderson; Romina Aron Badin; Hagai Bergman; Ashley Boehringer; Simon Borgognon; Marina E. Emborg; Jeffrey H. Kordower; Jia-Yi Li; Anne-Caroline Martel; Jeanette M. Metzger; Yoland Smith; et al. (npj Parkinson's Disease)
Abstract The PD-AGE international task force underscores the pivotal role that non-human primate (NHP) models play in advancing our understanding of Parkinson’s disease (PD) and ageing. Due to their close genetic, anatomical, and behavioural similarity to humans, NHPs uniquely enable translational research to bridge basic science towards clinical application. They are indispensable for modelling the complex motor and non-motor symptoms of PD, as well as age-related neurodegeneration. This paper outlines the scientific rationale, methodological strengths, and ethical considerations surrounding NHP use in PD research. We highlight the need for standardised models, innovative tools, and long-term collaborative infrastructure to enhance the translational value of NHP studies. We propose a three-phase roadmap to develop a global research consortium to optimise resource use, improve model fidelity, and accelerate therapeutic development for PD and related neurodegenerative disorders.